"Three-Step Approach" Versus "See-and-Treat Procedure" in women with "High Grade Squamous Intraepithelial Lesion" (HSIL) or "Atypical Squamous Cells cannot exclude HSIL" (ASC-H) Cytology - Mustafa Erkan Sari; Ibrahim Yalcin; Hanifi Sahin; Mehmet Mutlu Meydanli; Tayfun Gungor (Medical Network, 2018)
Objective: The purpose of this study was to examine the correlation between histological findings in women with HSIL or ASC-H who have undergone loop electrosurgical excisional procedure with "Three-Step Approach" and "See-and-Treat Procedure". Study Design: A retrospective review was performed in 171 women with cytologically detected HSIL or ASC-H. Sixty five women with HSIL cytology and 35 women with ASC-H cytology were managed by "Three-Step Approach", 35 women with ASC-H and 36 women with HSIL cytology were managed by "See-and-Treat Procedure". Rates of histopathological findings were compared in two strategies with respect to previous cytology. Results: Fifteen women with ASC-H (42.9%), and 24 women with HSIL (68.5%) had CIN 2-3 at loop electrosurgical excisional procedure specimens in the "See-and-Treat" group whereas 14 women with ASC-H (38.8%), and 43 women with HSIL (66.2%) had CIN 2-3 at loop electrosurgical excisional procedure specimens in the "Three-Step Approach" group. There was no significant difference in the rate of CIN 2+ lesions when two strategies were compared in women with HSIL and ASC-H (p=0.71 and p=0.72, respectively). The overtreatment rates were 22.9% and 48.6% for HSIL and ASC-H cytology, respectively in the "See and Treat" group. Conclusion: In the ASC-H group, the rate of CIN 2+ lesions is significantly high (51.4%). It seems rational to perform "See-and-Treat procedure" in the setting of ASC-H smears although the overtreatment rate seems to be high. Because of the rate of overtreatment, the "Three-Step Approach" seems to be more reasonable in women with ASC-H cytology who also have fertility concerns. After a cytological diagnosis of HSIL, "see and treat" approach seems to be a safe and time saving strategy.